METODOLOGI TAFSIR KONTEMPORER (Aplikasi Teori Hermeneutika Nashr Hamid Abu Zaid Q.S. An-Nisa: 3) - Wely Dozan (JOURNAL OF QUR'AN AND HADITH STUDIES, 2017)
Interpretation Q.S. an-Nisa '4: 3 in the discourse of interpretation always discussed both classical and contemporary interpretations. The verse is always legitimized as a polygamy verse. But among some contemporary thoughts such as Nasr Hamid Abu Zaid point out that, the verse is not an order against polygamy but rather in the context of marriage it is recommended for monogomy. Specifically, there are five hermeneutic approaches offered by Nasr Hamid Abu Zaid, socio-cultural contexts, external contexts, internal contexts, language contexts, and contexts of reading and reading. The research approach is the literature study approach which is a series of approaches relating to searching various sources of writing, whether in the form of books, articles, journals, or documents relevant to the problem under study. Thus, it can be concluded that, the application of Nazr Hamid Abu Zaid hermenutics to the interpretation of Q.S. An-Nisa '4: 3 is understood as a monogamous context rather than a command against polygamy.